Saliva microbiome alterations in dental fluorosis population - Shanshan Liu; Qiangsheng Song; Chenchen Zhang; Mengwan Li; Zhenzhen Li; Yudong Liu; Li Xu; Xiaofei Xie; Lili Zhao; Rongxiu Zhang; Qinglong Wang; Guojin Zeng; et al. (Journal of Oral Microbiology, 2023)
ABSTRACTBackground We aimed to explore saliva microbiome alterations in dental fluorosis population.Methods The prevalence of dental fluorosis was examined in 957 college students. Dean’s fluorosis index was used to evaluate the dental fluorosis status. Changes in the composition of the salivary microbiome were assessed in a subset of these patients (100 healthy controls, 100 dental fluorosis patients).Results Dental fluorosis affected 47% of the student sample, and incidence was unrelated to gender. Compared with healthy controls, the microbiota of patients with dental fluorosis exhibited increased diversity, with increased abundance of Treponema lecithinolyticum, Vibrio metschnikovii, Cupriavidus pauculus, Pseudomonas, Pseudomonadaceae, Pseudomonadales, and decreased abundance of Streptococcus mutans, Streptococcus sanguinis, Gemella, and Staphylococcales. Function analyses showed increases in arginine biosynthesis in patients affected by dental fluorosis, together with reductions in amino sugar and nucleotide sugar metabolism, fructose and mannose metabolism, and starch and sucrose metabolism.Conclusions These results suggest that there are striking differences in salivary microbiome between healthy controls and dental fluorosis patients. Dental fluorosis may contribute to periodontitis and systemic lung diseases. There is a need for cohort studies to determine whether altering the salivary microbiota in dental fluorosis patients can alter the development of oral or systemic diseases.